The witness - Roberts, Nora. (New York : G.P. Putnam's Sons, 2012)
Daughter of a controlling mother, Elizabeth finally let loose one night, drinking at a nightclub and allowing a strange mans seductive Russian accent lure her to a house on Lake Shore Drive. The events that followed changed her life forever. Twelve years later, the woman known as Abigail Lowery lives on the outskirts of a small town in the Ozarks. A freelance programmer, she designs sophisticated security systems. She keeps to herself, saying little, revealing nothing. But Abigails reserve only intrigues police chief Brooks Gleason. Her logical mind, her secretive nature, and her unromantic viewpoints leave him fascinated but frustrated.
Keywords: Child witnesses -- Fiction; Mafia -- Fiction; Murder -- Investigation -- Fiction; Police chiefs -- Arkansas -- Fiction; Arkansas -- Fiction; Romantic suspense fiction